Difficulties in psychotherapy with a residual schizophrenic - Schock, Sandra Lynn (Rhodes University, Faculty of Humanities, Department of Psychology, 1991)
This work addresses some of the difficulties encountered while working in psychotherapy with a residual schizophrenic. While there is an abundance of literature on psychotherapy for schizophrenia, both supporting and also refuting its merit, what the literature fails to reveal is that there appears to be a class of schizophrenic who, while apsychotic and able to communicate in the everyday sense of the word, is in a psychic space which speaks of a break with the basic relational elements of the human order. The quality of the patient's psychic life is such that almost nothing of what the literature describes as useful and appropriate in working with schizophrenics seems to help in the psychotherapeutic work with this type of patient. This study describes these issues with relevance to a particular residual schizophrenic. The Illustrative-didactic case-study method was used to discuss the four-and- a-half month psychotherapy with this patient. The patient's early developmental history, premorbid personality functioning, family and interpersonal relationships, mental state, diagnosis and a rationale for psychotherapy were presented and considered in detail. The structure of the psychotherapeutic process was reviewed in depth. The hermeneutic guidelines to understanding the case were drawn from Object-Relations Psychoanalytic theory, particularly Balint, Khan, Karon & VandenBos, Bollas, Romanyshyn, Perry, Symington, Fordham and others. Various psychic and personality features, as unveiled through the psychotherapeutic process, were elaborated and the implications of these for the therapeutic endeavour were considered as follows: Firstly, the psychic space of the patient, which precluded mirroring, symbolization find object-relationship - and which made psychotherapy untenable, was discussed. Secondly, therapeutic ambivalence and other counter-transference issues were reviewed. Thirdly, the shadow sides of both therapeutic optimism and of psychotherapeutic change were considered. Fourthly, the issues of therapeutic failure and of other treatment possibilities for a residual schizophrenic patient were examined. It was concluded that there needs to be an important countertransference shift with regard to the psychotherapeutic goals for those patients whose condition may be chronic, and for whom it appears that psychotherapy is not going to be of any therapeutic benefit - find where an 'empathic accompaniment' might be as much as it is possible to hope for or achieve.
Keywords: Schizophrenics; Schizophrenia -- Treatment; Psychotherapy